Peran Joint Attention dalam Kemampuan Bahasa Anak Autism Spectrum Disorder: Studi Literatur - Oktariani; Lodiana Ayu; Fenty Zahara Nasution; Dea Fatwana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
For children with Autism Spectrum Disorder, speech delays are not the only communication issue. Often, nonverbal communication—which includes body language, eye contact, facial expressions, and body movements—poses challenges. Joint attention is crucial for a child’s development, whether the child is neurotypical or has an autism spectrum disorder, particularly in the development of language and social communication. This study employs a qualitative method in the form of a literature review. Previous research has found that the lower the level of joint attention demonstrated by children diagnosed with autism spectrum disorder, the more severe their social and communication difficulties become. Children with autism spectrum disorder typically experience difficulties with joint attention. Joint attention is the skill of sharing focus or attention on an object or event with another person. Behaviors such as pointing, following another person’s gaze or vocalizations, and directing one’s gaze toward a specific object or event are among the early social-communicative behaviors included in this skill. Joint attention is crucial for children’s language, communication, and cognitive development